PENDIDIKAN KECAKAPAN HIDUP DI PESANTREN DARUL HIKAM BANJARAN BANDUNG - Juju Saepudin (Badan Litbang dan Diklat Kementerian Agama RI, 2016)
abstrakPesantren as one of the institutions of Islamic education in Indonesia is considered to have contributed quite signiicantly in the development of national education. However, the issue encountered by people from various social stratiications in education, including pesantren, is the low quality and relevance of education to the labor market needs. In fact, many pesantren alumni have no choice of employment to meet their needs in the real life. This paper presents the results of research on independence-based education life skills and local potential in Pesantren Darul Hikam Banjaran Bandung regency. The study was conducted using qualitative approach and case study designed naturalistically. Data was collected through observation, interview and documentation methods. Inductive data analysis identiied models of life skills education for students with self-reliance and local potential capitals. Two-wheeled vehicle mechanical skill in Pesantren Darul Hikam that uses local curriculum with a ratio of 20% theory and 80% practice empowers senior students to be the teachers assisted by local BLK has been able to equip the students with skills in automotive detailing allowing them to be ready to enter the professional world.Keywords: education, Life skills, PesantrenabstrakPesantren sebagai salah satu lembaga pendidikan Islam di Indonesia dinilai memiliki kontribusi yang tidak kecil dalam pembangunan pendidikan nasional. Namun persoalan masyarakat dari berbagai stratiikasi sosial dalam dunia pendidikan termasuk pesantren adalah rendahnya mutu dan relevansi pendidikan dengan kebutuhan pasar kerja. Bahkan, banyak alumni pesantren yang tidak memiliki pilihan lapangan kerja untuk menenuhi kebutuhan hidupnya di masyarakat. tulisan ini menyajikan hasil penelitian tentang pendidikan kecakapan hidup berbasis kemandirian dan potensi lokal di Pesantren Darul Hikam Banjaran Kabupaten Bandung. Penelitian dilakukan dengan menggunakan pendekatan kualitatif dan rancangan studi kasus yang bersifat naturalistik. tehnik pengumpulan melalui pengamatan, wawancara mendalam dan metode dokumentasi. Analisa data secara induktif menemukan model pendidikan kecakapan hidup bagi santri dengan modal kemandirian dan potensi lokal. Pendidikan kecakapan hidup otomotif roda dua di Pesantren Darul Hikam menggunakan kurikulum lokal dengan perbandingan 20 % teori dan 80 % praktek, memberdayakan santri senior sebagai guru dan dibantu dari BLK setempat telah mampu membekali keterampilan santri dibidang otomotif sehingga siap memasuki dunia kerja.Kata Kunci: Pendidikan, Kecakapan Hidup, Pesantren